1986
DOI: 10.1007/bf00237580
|View full text |Cite
|
Sign up to set email alerts
|

The orientation of the cervical vertebral column in unrestrained awake animals

Abstract: The orientation of the cervical vertebral column was studied by X-ray photography of the region containing the head and the neck in nine unrestrained species of vertebrates (man, monkey, cat, rabbit, guinea pig, rat, chicken, frog, lizard). In addition, the orientation of the horizontal semicircular canals was measured in four species using landmarks on the skull. In all vertebrates studied, with the exception of frog and lizard, the general orientation of the cervical vertebral column was vertical when animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
145
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(151 citation statements)
references
References 17 publications
6
145
0
Order By: Relevance
“…Bonnet macaques and hanuman langurs, members of two separate phylogenetic subfamilies (Cercopithecinae and Colobinae, respectively) and who differ in body size and proportions, nevertheless practice comparable head and trunk movement patterns during walks and gallops (Dunbar et al, 2004). This finding is consistent with the combined experimental evidence from other studies that the neural mechanisms underlying dynamic posture (Dunbar et al, 1986), locomotion (e.g., Peters and Goslow, 1983;Vilensky and Gehlsen, 1984) and gaze (Vidal et al, 1986) are conservative in organization among tetrapods. Cercopithecus aethiops is not a phylogenetically distant species differing so dramatically in morphology and lifestyle that differences in sensorimotor capabilities would be expected.…”
Section: Comparison Of Vervet Treadmill Locomotion With Overgroundsupporting
confidence: 86%
“…Bonnet macaques and hanuman langurs, members of two separate phylogenetic subfamilies (Cercopithecinae and Colobinae, respectively) and who differ in body size and proportions, nevertheless practice comparable head and trunk movement patterns during walks and gallops (Dunbar et al, 2004). This finding is consistent with the combined experimental evidence from other studies that the neural mechanisms underlying dynamic posture (Dunbar et al, 1986), locomotion (e.g., Peters and Goslow, 1983;Vilensky and Gehlsen, 1984) and gaze (Vidal et al, 1986) are conservative in organization among tetrapods. Cercopithecus aethiops is not a phylogenetically distant species differing so dramatically in morphology and lifestyle that differences in sensorimotor capabilities would be expected.…”
Section: Comparison Of Vervet Treadmill Locomotion With Overgroundsupporting
confidence: 86%
“…This value accords with the observation that most species position their heads so as to hold the plane of the horizontal semicircular canal horizontal. A previous study of posture in mice concluded that they carry their horizontal canals oriented 15° upwards during rest and locomotion (Vidal, et al, 2004), while a study of Long-Evans rats yielded a value of 14° ( Rabbath, et al, 2001), and a comparative study of several mammalian and non-mammalian species found an average upwards pitch of about 5°, although there was a large degree of moment-to-moment variation (Vidal, et al, 1986).…”
Section: Natural Position Of the Head And The "Rest" Position Of The mentioning
confidence: 98%
“…It may be significant that the eye elevation of 29° falls close to the midpoint of the range of vertical eye positions achieved over the entire range of pitch orientations (figure 1a), suggesting that the animal normally adjusts its head to place the eyes at the center of the range of the tiltMOR. Alternatively, the tiltMOR may have been optimized by an evolutionary process so that the midpoint of the variation of eye elevation coincides with the average head orientation during ambulation, which in turn may be dictated by the constraints of skeletal geometry (Vidal, et al, 2004;Vidal, et al, 1986). It is also interesting that the horizontal resting angle of 64° occupies something of a special position in the plots of horizontal eye orientation versus tilt angle, coinciding, as it does, with the approximate temporal limit in response to roll and the nasal limit in response to pitch tilts.…”
Section: Natural Position Of the Head And The "Rest" Position Of The mentioning
confidence: 99%
“…Radiographic studies of the head and neck in alert mammals (e.g., cats, guinea pigs, rats, and some monkey species) have demonstrated instead that the cervical region can display complex curvatures and is often maintained, at least in resting positions, in a more vertical alignment (Vidal et al, 1986). This morphology is argued to indicate a more energetically efficient biomechanical system analogous to that of a suspension bridge or inverted bow-and-string !…”
mentioning
confidence: 99%
“…Another mechanism to consider is the curvature(s) in the cervical column. The presence of such curvature is an important reminder that the pronograde primate neck is not necessarily a simple beam held in a near-horizontal orientation out from the torso.Radiographic studies of the head and neck in alert mammals (e.g., cats, guinea pigs, rats, and some monkey species) have demonstrated instead that the cervical region can display complex curvatures and is often maintained, at least in resting positions, in a more vertical alignment (Vidal et al, 1986). This morphology is argued to indicate a more energetically efficient biomechanical system analogous to that of a suspension bridge or inverted bow-and-string !…”
mentioning
confidence: 99%